The impact of single‑nucleotide polymorphisms on liver stiffness and controlled attenuation parameter in patients treated with direct‑acting antiviral drugs for hepatitis C infection. Issue 2 (18th November 2021) - MATSUMOTO, KOSUKE; MIYAAKI, HISAMITSU; FUKUSHIMA, MASANORI; SASAKI, RYU; HARAGUCHI, MASAFUMI; MIUMA, SATOSHI; NAKAO, KAZUHIKO
No abstract available